Slow cooling and efficient extraction of C-exciton hot carriers in MoS2 monolayer - Lei Wang (Nature Portfolio, 2017)
Light-matter interaction in atomically thin transition metal dichalcogenides is dominated by excitonic effects and hot-carrier relaxation/extraction mechanisms. Here, the authors report that the C exciton in two-dimensional MoS2exhibits a slower hot-carrier cooling than band-edge excitons.